Smart School Management Through Digital Transformation: A Case Study of Nasima Elementary School, Semarang City - Damayanti, Dwi Farisa; Wuryandini, Endang; Ginting, Rosalina Br (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study evaluates the implementation of smart school management through digital transformation at Nasima Elementary School (SD Nasima), Semarang City, focusing on the managerial processes of planning, organizing, implementing, and supervising the school’s digitalization. Methods: This qualitative case study employed various data collection techniques, namely observation, in-depth interviews, and documentation, to comprehensively investigate the management strategies applied throughout the digital transformation process. Results: SD Nasima has successfully integrated digital technologies into its curriculum, infrastructure, and school management. The implementation of a Learning Management System, smartboards, and other digital tools has enhanced the effectiveness of the teaching and learning process. However, challenges remain in areas such as teachers’ digital skills, team coordination, and the allocation of resources for continuous training and support. Well-structured planning, clear organization, effective implementation, and consistent supervision influence the success of digital integration. Novelty: This study presents a comprehensive digital transformation management model at the elementary school level based on a local case study approach, which remains underexplored in the context of Indonesian basic education. This provides practical insights for schools seeking to adopt similar approaches to educational digitalization.